Are small carnivores urban avoiders or adapters: Can they be used as indicators of well-planned green areas?. (June 2019) - Łopucki, Rafał; Klich, Daniel; Kitowski, Ignacy
Highlights: The response of small carnivores to urban environments is poorly studied. We tested an effect of land cover, food base and built-up area on the least weasel occurrence. Weasels colonize only non-isolated fragments of urban environment. Food base (abundance of rodents) also limit the occurrence of weasels. The occurrence of weasel can be an indicator of well-planned urban greenery. Abstract: Terrestrial mammalian carnivores are generally sensitive to urbanization. Yet, some mesocarnivores have adapted to the urban and suburban environment. The response of small carnivores to urbanization is poorly studied, partly due to methodological difficulties. We assessed the impact of urbanization on a representative of small carnivores – the least weasel Mustela nivalis . Data from 254 trapping sessions of monitoring small mammals (27 810 trap-days) conducted in different urbanized and non-urbanized habitats (Poland, Central Europe) were used and analysed in a logistic regression model. The probability of occurrence of weasels was tested in relation to the land cover type, abundance of rodents (weasel's food base), proportion of a built-up area (on the 500 m radius buffer) and trapping effort. The weasel avoided urban areas and if the percentage of a built-up area was higher than 32% the probability of occurrence of the weasel was low (P < 0.5). Within urbanized areas, least weasel were only detected on the outskirts of a city or in the valleys of large rivers. Conversely, habitat type did not predict the presence of least weasel in non-urbanized areas. The possible reasons for the lack of the weasel in urban green areas are narrow food specialization (mainly rodents as prey; no use of anthropogenic food sources), high energetic demands, and fragmentation and isolation of green areas. Despite the high ecological plasticity of this species, the strong negative response of the least weasel to urbanization causes that their occurrence can be an indicator of well-planned urban greenery. The occurrence of the least weasel indicates both the functional connectivity of green areas in the city and the abundance and availability of the prey base – ground-dwelling animals from lower trophic groups.